[(Flu)-(CH2)2-(NHC)-CH2-(NHC)-(CH2)2-(Flu)]2−: an 'all-organic' hybrid and flexible ligand that enwraps a Ca2+ pseudo-tetrahedrally. Issue 87 (13th October 2022) - Baguli, Sudip; Das, Shovan; Chakraborty, Mahua; Goswami, Santu; Datta, Ayan; Mukherjee, Debabrata
Abstract : A conformationally flexible ligand, [(Flu)-(CH2 )2 -(NHC)-CH2 -(NHC)-(CH2 )2 -(Flu)] 2− (L), that offers four sequential organic donor modules and enwraps a Ca 2+ pseudo-tetrahedrally in a twisted 'S'-shape is devised. Abstract : A conformationally flexible ligand, [(Flu)-(CH2 )2 -(NHC)-CH2 -(NHC)-(CH2 )2 -(Flu)] 2− (L), that offers four sequential organic donor modules and enwraps a Ca 2+ pseudo-tetrahedrally in a twisted 'S'-shape is devised. The [(L)Ca] synthesis is intriguingly stepwise involving the intermediate [(LH)Ca(HMDS)], whereas [(LH)Li2 (HMDS)] shows the potential for bimetallic chemistry. The bonding is illustrated by energy decomposition analyses.